PENENTUAN RANGE DOSIS IMUNOSTIMULAN DAN LAMA WAKTUPERENDAMAN TERBAIK PADA EKSTRAK KASAR FENOLGracilaria sp. SEBELUM UJI TANTANG BAKTERI Aeromonas sp. DENGAN MENGGUNAKAN LC50 - Ismaningdyah Kurniawati; Maftuch Maftuch; Anik Martinah Hariati (Samakia : Jurnal Ilmu Perikanan, 2017)
Immunostimulatory dose given to the fish to be precise, should not be less and should not be excessive. This is because the immunostimulatory properties which can only work at the optimal dose.Therefore,themethod fordetermining the dosage and administration techniques immunostimulatory should be studied in depth.Research on the determination of the dose and the best maceration time on the crude extract phenol Gracilaria sp. using LC50 is intended to determine how best dose and how long it's best used in the immersion process to extract.rangedose used is 1 g/l; 1,5 g/l; 2 g/l; 3 g/l; 4 g/l and 5 g/l.The results of these observations indicate that doses ≥ 3 g/l has a 10-hour LC50.While the dose ≤ 3 g/l has a 14-hour LC50.However, further research is continued in the time range for prolonged submersion namely 10, 12 and 14 hours.The results showed the soaking time 12 hours showed LC50 15 hours.It concluded that the dose that can be used to test immunostimulant is 1, 1.5 and 3 g/l with a soaking time of less than 12 hours.